STRATEGY FOR INCREASING THE FUNDRAISING OF CURRENT ACCOUNT PRODUCT AT PT BANK XYZ KCP A MEDAN - Intan, Anni; Sembiring, Meilita Tryana; Nazaruddin, Nazaruddin (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2023)
Business competition in the domestic and international markets is increasingly competitive in the current era of globalization and digitalization where every company is required to be able to meet consumer needs and strive to create a product that has advantages and is different from its competitors. The banking services industry in the future will face increasing, varied and dynamic challenges. This challenge has had a more significant impact since the Covid-19 pandemic due to the large-scale social restriction policy imposed by the government. The banking services industry must face structural challenges such as business scale and banking competitiveness, economic developments and changes in people's economic behavior that have shifted to digital finance.